Effectiveness of Physical Therapy with Kinesio Taping in the Treatment of Patients with Knee Ligament Injuries - Cherniak, V.P.; Stepanova, H.M.; Dashko, K.S.; Kravets, A.O. (TERRA ORTHOPAEDICA, 2025)
Background. Kinesio taping is a therapeutic technique gaining popularity in knee injury treatment. The method is based on the use of a highly elastic adhesive material that allows free mobility of the treated body area. Objective. The aim of this study was to evaluate the effectiveness of kinesio taping in restoring joint functionality. Materials and Methods. A comparative analysis was conducted between two groups of patients: the control group (basic rehabilitation) and the experimental group (basic rehabilitation with kinesio taping). Results. At baseline, both groups had comparable clinical and functional indicators, including pain level, the Oswestry Disability Index, knee joint range of motion, and muscle strength. After the rehabilitation course, both groups demonstrated positive dynamics, with knee flexion amplitude improving by approximately 90% and extension by 70%. However, the kinesio taping group demonstrated statistically significant advantages: muscle strength increased by 36.46% (versus 14-17% in the control group), Lower Extremity Functional Scale scores improved by 44.55% (versus 5.33%), postural stability increased by 29.85% (versus 0.73%), and Hauser’s walking index improved by 30.51% (versus 3.33%). No statistically significant between-group differences were found in pain reduction (approximately 49% in both groups) and improvement in the Oswestry Disability Index (approximately 52%). Discussion. These results can be explained by the fact that kinesio taping provides additional proprioceptive stimulation and mechanical support during rehabilitation exercises, facilitating more effective recovery of muscle strength and postural control. Conclusions. The study confirms that incorporating kinesio taping into comprehensive rehabilitation program significantly enhances its effectiveness, particularly in restoring muscle strength, postural control and overall lower limb functionality, although showing no advantages in pain control or certain specific functional parameters compared to standard rehabilitation programs. These findings have important practical implications for optimizing rehabilitation protocols and rational use of kinesio taping in physical therapy for patients with knee ligament injuries.